THE UTILIZATION OF WEBTOON DIGITALCOMIC IN READING COMPREHENSION: WHAT ARE THE PERCEPTIONS OF THE STUDENTS? - Savitri, Fachrina; Zaitun, Zaitun (Universitas Tanjungpura, 2024)
This study aimed to analyse students' perceptions on the utilization of Webtoon digital comics media in their reading comprehension. This research used qualitative method with case study design. The data were collected by using a 5-Likert scale questionnaire and semi-structured interview asking about students